Analysis Analysis of Factors Influencing Student Anxiety in Facing the OSCE Exam: A Study on Diploma Among Nursing Students at STIKES Kamus Arunika - Hairuddin Safaat; Hardin; Hardianto Dg. Salimung (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Anxiety in facing the Objective Structured Clinical Examination (OSCE) remains a significant challenge for nursing students. Recent studies show that anxiety among nursing students facing the OSCE is high. The report shows that 75.5% of students experienced moderate anxiety when facing the OSCE. This study aimed to analyze the influence of self-efficacy, academic readiness, academic motivation, and social support on students’ anxiety. A cross-sectional correlational design was used, involving 94 Diploma in Nursing students at STIKES Kamus Arunika. Data were collected using structured questionnaires and analyzed using Pearson correlation and multiple linear regression. The results showed that anxiety levels were categorized as moderate in 62 students (66.0%), high in 27 students (28.7%), and low in 5 students (5.3%). All independent variables were significantly negatively correlated with anxiety, with self-efficacy showing the strongest relationship (r = -0.345, p < 0.01). Regression analysis revealed that self-efficacy (β = -0.312; p = 0.001), academic readiness (β = -0.224; p = 0.024), academic motivation (β = -0.215; p = 0.032), and social support (β = -0.162; p = 0.045) were significant predictors, explaining 37.4% of the variance in anxiety (R² = 0.374). These findings highlight the integrated role of psychological, academic, and social factors in shaping student anxiety, with self-efficacy as the most influential determinant. This study contributes an integrative perspective and suggests that targeted interventions, including self-efficacy enhancement, structured OSCE preparation, and supportive learning environments, are essential to reducing anxiety and improving student performance.